Legal Uncertainty of Foreign Investors Before Company Ratification in Indonesia: Ketidakpastian Hukum bagi Investor Asing Sebelum Pengesahan Perusahaan di Indonesia - Tanuwijaya, Jessica; Adam, Richard C. (Indonesian Journal of Law and Economics Review, 2025)
General Background: Foreign investment plays a pivotal role in fostering Indonesia’s economic growth by enhancing technology transfer, employment, and national development. Specific Background: Despite the enactment of Law No. 25 of 2007 on Investment and Law No. 40 of 2007 on Limited Liability Companies, legal uncertainties persist, particularly when the Deed of Establishment of a Limited Liability Company (PT) has not been ratified by the Minister of Law and Human Rights. Knowledge Gap: Previous studies rarely examine the legal standing and protection of foreign investors during the transitional phase before company ratification, creating ambiguity in their legal recognition. Aims: This study aims to analyze the legal status and barriers to legal protection for foreign investors whose company’s deed of establishment has not been ratified, under Indonesia’s Investment Law. Results: The findings reveal that unratified companies lack legal personality and protection, rendering contracts voidable and exposing founders to personal liability. Legal uncertainty is further aggravated by regulatory disharmony, administrative inefficiencies, and unsynchronized digital systems between ministries. Novelty: This study elucidates the intersection between corporate ratification processes and investor protection, highlighting gaps in the registration-based system introduced by the Job Creation Law. Implications: The research underscores the necessity for harmonized regulations, streamlined digital governance, and stronger legal safeguards to promote investor confidence and ensure Indonesia’s economic resilience. Highlights:   Unratified companies lack legal standing and expose founders to personal liability. Regulatory disharmony and system inefficiencies hinder legal certainty for investors. Harmonized and transparent legal frameworks are vital to strengthen investor confidence. Keywords: Legal Status, Foreign Investors, Investment Law, Company Ratification, Legal Protection